2006
DOI: 10.1128/jb.188.4.1551-1566.2006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Transcriptional Analysis of the Siderophore Malleobactin Biosynthesis and Transport Genes in the Human Pathogen Burkholderia pseudomallei K96243

Abstract: Burkholderia pseudomallei is a gram-negative facultative intracellular pathogen that causes melioidosis, an invasive disease of humans and animals. To address the response of this bacterium to iron-limiting conditions, we first performed a global transcriptional analysis of RNA extracted from bacteria grown under iron-limiting and iron-rich conditions by microarrays. We focused our study on those open reading frames (ORFs) induced under iron limitation, which encoded predicted proteins that could be involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 71 publications
(54 reference statements)
6
73
0
Order By: Relevance
“…The presence of a Fur box overlapping the putative promoter for bhuR suggests that the haem uptake system of B. pseudomallei is induced in response to iron starvation. Consistent with this, microarray analysis has shown that transcription of BPSS0243 (bhuS) and BPSS0244 (bhuR) is induced under iron-limiting conditions (Tuanyok et al, 2005;Alice et al, 2006). It has been observed previously that iron acquisition genes are required by other intracellular pathogens, such as Legionella pneumophila, for growth within macrophages (Pope et al, 1996).…”
Section: Discussionsupporting
confidence: 56%
“…The presence of a Fur box overlapping the putative promoter for bhuR suggests that the haem uptake system of B. pseudomallei is induced in response to iron starvation. Consistent with this, microarray analysis has shown that transcription of BPSS0243 (bhuS) and BPSS0244 (bhuR) is induced under iron-limiting conditions (Tuanyok et al, 2005;Alice et al, 2006). It has been observed previously that iron acquisition genes are required by other intracellular pathogens, such as Legionella pneumophila, for growth within macrophages (Pope et al, 1996).…”
Section: Discussionsupporting
confidence: 56%
“…However, in contrast to the pyochelin receptor, synthesis of which is inducible by its cognate iron-loaded siderophore (Heinrichs and Poole 1996;Michel et al 2005), orbA gene expression is not stimulated by the presence of ferric-ornibactin, and the ability to utilise ornibactin is not a prerequisite for production of ornibactin (Sokol et al 2000). Similar observations have been made regarding the malleobactin receptor of B. pseudomallei (Alice et al 2006). Transport of ornibactin across the cytoplasmic membrane is likely to be specified by the orbB, orbC and orbD genes (BCAL1694, BCAL1691 and BCAL1692, respectively).…”
Section: Ornibactinmentioning
confidence: 57%
“…The TonBdependent pyochelin outer membrane receptor, FptA, and/or its gene, have been identified in P. aeruginosa, P. fluorescens, B. cenocepacia and B. pseudomallei (Heinrichs et al 1991;Ankenbauer 1992;Ankenbauer and Quan 1994;Visser et al 2004;Paulsen et al 2005;Alice et al 2006). Additionally, Southern hybridisation experiments have identified the presence of the fptA gene in the genomes of P. aureofaciens, P. putida and B. cepacia 25416, although P. aureofaciens and P. putida are not known to produce pyochelin (Castignetti 1997).…”
Section: Pyochelinmentioning
confidence: 95%
See 2 more Smart Citations